2022
DOI: 10.1093/hr/uhab065
|View full text |Cite
|
Sign up to set email alerts
|

Methylation related genes affect sex differentiation in dioecious and gynodioecious papaya

Abstract: Morphological, genic and epigenetic differences often exist in separate sexes of dioecious and trioecious plants. However, the connections and relationships among them in different breeding systems are still unclear. Papaya has three sex types, which is genetically determined and epigenetically regulated, and was chosen as a model to study sex differentiation. Bisulfite sequencing of genomic DNA extracted from early-stage flowers revealed sex-specific genomic methylation landscapes and seasonally methylome rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The sex in wild papaya is controlled by XY chromosomes, XX for females, and XY for males (Ming et al, 2008). Previous studies have suggested that sex differentiation in papaya may be regulated by transcription, epigenetic DNA methylation, and phytohormone by considering the experiments in above-ground parts (Zhou et al, 2020;Zhou P. et al, 2022). Zhou et al in this Research Topic have used transcriptomics and metagenomics to reveal differential metabolites and soil microflora (bacteria and fungi) in the roots and rhizosphere of male and female papaya plants.…”
Section: Research On Fruit Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sex in wild papaya is controlled by XY chromosomes, XX for females, and XY for males (Ming et al, 2008). Previous studies have suggested that sex differentiation in papaya may be regulated by transcription, epigenetic DNA methylation, and phytohormone by considering the experiments in above-ground parts (Zhou et al, 2020;Zhou P. et al, 2022). Zhou et al in this Research Topic have used transcriptomics and metagenomics to reveal differential metabolites and soil microflora (bacteria and fungi) in the roots and rhizosphere of male and female papaya plants.…”
Section: Research On Fruit Cropsmentioning
confidence: 99%
“…The sex in wild papaya is controlled by XY chromosomes, XX for females, and XY for males ( Ming et al., 2008 ). Previous studies have suggested that sex differentiation in papaya may be regulated by transcription, epigenetic DNA methylation, and phytohormone by considering the experiments in above-ground parts ( Zhou et al., 2020 ; Zhou P. et al., 2022 ). Zhou et al.…”
Section: Research On Fruit Cropsmentioning
confidence: 99%
“…Other studies have highlighted that DNA methylation is also a significant player in sexual differentiation and sex chromosome evolution. Whole-genome bisulfite sequencing of papaya early-stage flowers revealed that distinct phytohormone signaling pathways and differential methylation-related gene expression are thought to contribute to DNA methylation alterations in papaya 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The sex in wild papaya is controlled by XY chromosomes, XX for females, and XY for males ( Ming et al., 2008 ). Previous studies have suggested that sex differentiation in papaya may be regulated by transcription, epigenetic DNA methylation and phytohormone ( Zhou et al., 2020 ; Liu et al., 2021a ; Zhou et al., 2022 ). However, a vast majority of these studies have focused on the aboveground parts of dioecious plants such as flower buds, and shoot meristems, while few reports focused on the belowground parts.…”
Section: Introductionmentioning
confidence: 99%